2012
DOI: 10.7589/0090-3558-48.3.603
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Characterization of Klebsiella Pneumoniae Isolates Recovered From Nonhuman Primates

Abstract: ABSTRACT:Klebsiella pneumoniae is a zoonotic, Gram-negative member of the family Enterobacteriaceae and is the causative agent of nosocomial septicemic, pneumonic, and urinary tract infections. Recently, pathogenic strains of K. pneumoniae sharing a hypermucoviscosity (HMV) phenotype have been attributed to multisystemic abscessation in both human and nonhuman primates. Although K. pneumoniae is a well-recognized zoonotic agent, there is a lack of general information including adequate diagnostic methods or tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 16 publications
(13 reference statements)
0
19
0
Order By: Relevance
“…The hypermucovisity phenotype of K . pneumoniae has not been reported as the natural cause of diseases in NHPs but is characterized by a subclinical infection associated with virulence factors and evasion mechanisms used by the pathogen, and the innate immune system . This is exemplified by the ability of these bacteria to evade and survive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypermucovisity phenotype of K . pneumoniae has not been reported as the natural cause of diseases in NHPs but is characterized by a subclinical infection associated with virulence factors and evasion mechanisms used by the pathogen, and the innate immune system . This is exemplified by the ability of these bacteria to evade and survive.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, K. pneumoniae serotype K1 strain ST23 has not yet been reported as a pathogen in wild and captive NHP in Brazil. Complete genotyping and phenotyping characterization of the microorganism is essential to establish adequate diagnostic methods …”
Section: Introductionmentioning
confidence: 99%
“…Bacterial strains and culture conditions K. pneumoniae strains isolated from septicemic AGM with single or multifocal abscesses were isolated at the Ross University School of Veterinary Medicine Diagnostic Laboratory from 2010 to 2012. Identification of the isolates was made according to standard clinical microbiologic and molecular methods (Soto et al, 2012;Hartman et al, 2009). All isolates were suspended in brain-heart infusion broth (BHI) (Sigma-Aldrich, St. Louis, MO, USA) with a final concentration of 20% glycerol and stored at À80 8C before use.…”
Section: Animal Care and Usementioning
confidence: 99%
“…While African green monkeys (AGM), commonly used in biomedical research worldwide, have been reported with fatal multisystemic abscesses caused by HMV serotypes of K. pneumoniae (Twenhafel et al, 2008;Hartman et al, 2009;Soto et al, 2012) very little is known about the pathogenesis of HMV K. pneumoniae infection in this host. To gain a better understanding about the pathogenesis of this important emergent disease in primates, we compared specific components of the AGM innate immune response to HMV and non-HMV K. pneumoniae isolates previously recovered from clinically affected AGM.…”
mentioning
confidence: 99%
“…As in humans, infections of the respiratory tract, urinary tract, sepsis, and abscesses are the most common infection types [38,39]. K. pneumoniae is also of particular concern in dairy farms as it causes mastitis and leads to loss of milk production and death of affected livestock [4042].…”
Section: Introductionmentioning
confidence: 99%